PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA MELALUI PENERAPAN RPP DENGAN MODEL GROUP INVESTIGATION BERBASIS PENDIDIKAN KARAKTER DI KELAS XII IPA 1 SMA NEGERI 5 BENGKULU SELATAN TAHUN PELAJARAN 2014/2015 - Umran Umran (PAKAR Pendidikan, 2015)
Mathematics is a study material which has an abstract object and is constructed through a process of deductive reasoning, that the truth of a concept is obtained as a logical result of the truth previously been received, so that the relationship between concepts in mathematics are very strong and clear. Learning math is not just put on absorption through the attainment of information, but more emphasis on the development of capabilities and information processing. Therefore the student activity should be increased through exercises or mathematical tasks by working groups and explaining ideas to others. The aim of Classroom Action Research is to determine the increase in students' mathematics learning outcomes through the implementation of the RPP group investigation model of education based on the characters and want to know the impact of learning activities of students after applied RPP group investigation model based character education in class XII IPA 1 SMA N 5 South Bengkulu school year 2014/2015. This classroom action research conducted in two cycles. From the results of action taken proven to improve student achievement of learning outcomes by achieving the ideal standard. From 74.07% in Cycle I, can be increased in the second cycle to 100% with the achievements of the average value of student learning outcomes by 78, 296 in the first cycle and 87.63 in the second cycle and have achieved mastery in classical studies or indicators set. This action research results show that the application of the RPP with Group Investigation model-based character education proved effective in increasing the activity and results of students' mathematics learning and practical because it can be implemented properly in SMA N 5 South Bengkulu.